Pharmacokinetic drug evaluation of CVT-301 for the treatment of Parkinson's disease. (2nd December 2018) - Stocchi, Fabrizio; Vacca, Laura; Stirpe, Paola; Torti, Margherita
ABSTRACT: Introduction : Levodopa (LD), in combination with a decarboxylase inhibitor, is a mainstay and the most effective therapeutic agent in the treatment of Parkinson's disease (PD). Unfortunately, during chronic treatment with this agent, ON–OFF phenomena and dyskinesia appear. Despite the many medical treatment options available, unpredictable OFF episodes can still occur and be severe and disabling. A rescue therapy that provides a rapid and predictable ON response for patients with OFF periods would be of great value for such patients. Areas covered : CVT-301 is a self-administered dry powder aerosol inhaled formulation of LD that is being developed as a self-administered treatment for OFF periods. The PK profile of CVT-301, the efficacy, and the safety highlighted in randomized clinical trials will be reviewed. Expert opinion : CVT-301 may offer several potential advantages including increased systemic bioavailability through pulmonary absorption, rapid onset of action, avoidance of first-pass drug metabolism and less plasma-level variability. List of Abbreviations: PD: Parkinson's disease; LD: Levodopa; CD: Carbidopa; AADC: aromatic L-amino acid decarboxylase; IR: immediate-release; FPD: fine particle dose; GI: gastrointestinal; PK: pharmacokinetic; CVs: coefficient of variation; UPDRS: Unified Parkinson's Disease Rating Scale; AEs: adverse events; FEV: forced expiratory volume; FVC: forced vital capacity; DLCO : diffuse lung CO ; tmax : time to maximum concentration